Metafictional Games in Chatterton - Susana González Abalos (Miscelánea: A Journal of English and American Studies, 1993)
"Metafictional Games in Chatterton" is a study of Ackroyd’s Chatterton as a self-reflexive novel. This paper seeks to analyse the self-conscious narrative methods in Chatterton , focusing on Ackroyd’s choice of subject matter and on his rewriting of history. From a narratological approach, we see how the novel questions its own methods of representation, and the issue of representation in works of art, mainly in literature and painting. After a study of the figure of the poet Chatterton, we examine the relevance of his ideas on plagiarism in the present literary society depicted in the novel; plagiarism is a general condition in this poststructuralist society. The last part of the paper is devoted to a study of Chatterton as a historiographic metafictional novel, and is based on Hutcheon’s analysis of this narrative form.